(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article describes a creative approach to the educational process today, organizing the training process on the basis of cooperative pedagogy, which is a part of the new pedagogical technologies, aimed at developing children’s independence, organizing training at the level of modern requirements.